Investigation of photophysical and charge transport properties of optical spacers and plasmonic nanostructures in organic photovoltaics - Than, Zaw Oo (2013)
Whilst organic photovoltaics (OPV) offer several opportunities such as easy-to-tailor molecular properties, low-cost fabrication and mechanical flexibility, an extensive boost of power conversion efficiency (PCE) is of fundamental necessity to realize the commercialization of OPV devices. This thesis focuses on two approaches, incorporation of (i) titanium suboxide (TiOx) interfacial layer and (ii) plasmonic gold nanowires (Au-NWs), to improve the device efficiencies via modulation of optical and charge transporting properties in OPV devices. The PCE of ~ 6% was achieved in PCDTBT:PC71BM and PTB7:PC61BM devices. The sol-gel derived TiOx layer was integrated at the cathode interface of P3HT:PCBM, PCDTBT:PCBM and PTB7:PCBM devices. Firsdy, the role of TiOx optical spacer was investigated using the finite difference time domain (FDTD) optical simulation technique. The calculated and experimental absorption profiles show that optical spacer effect was more pronounced in the thinner active layer and diminished with increasing active layer thickness. The optical advantage of TiOx interfacial layer was not achieved once the active layer thickness has been optimized. The enhanced current density 0SC) with TiOx interlayer was attributed to the combined effect of optical spacer and charge transport across cathode interface. The first part of the thesis highlights the decoupling of optical and electrical contributions of TiOx to Jsc by using the optical reflectance and internal quantum efficiency (IQE) measurements. Decoupling of optical and electrical effects of interlayer would support further device optimization and designs including the evaluation of new interfacial layers.